SCAFFOLDING THROUGH WEBQUEST AS A MEANS TO DEVELOP STUDENTS' WRITING PERFORMANCE : A case study of WebQuest as Scaffolding for Students of a Madrasah Aliyah in Yogyakarta - Fakhmawati, Diah (2009)
Students have difficulties in writing; particularly to initiate the writing and develop the content of the writing. WebQuest is a strategy in learning which is supported by scaffolding. The scaffolding is intended to facilitate the students complete the task. This study investigates the feasibility of WebQuest to provide scaffolding for secondary students in writing activities. The study employed a qualitative research design in form of case study. The research was conducted in a Madrasah Aliyah in Yogyakarta. It involved eight students of grade XI enrolled in 2009 who voluntary participated. The research applied multiple data collection techniques. The data were collected from observation, interview and text analysis. The data show that WebQuest has facilitated the students by providing scaffolding through guiding directions in the stages, links of web resources, and student collaboration which emerges during WebQuest activities. The guiding directions provided in all stages give clear directions for the students and motivate them to keep on their writing task completion. The online resources linked in the WebQuest facilitate the students to improve reading skills, such as skimming and scanning. It also develops thinking skills such as evaluating and synthesizing which help the students construct the composition. Meanwhile the students collaboration prompted by the WebQuest activities has provided scaffolding to facilitate the students accomplish the writing task. The collaboration occurs in comprehending the task and the resources, and in drafting and revising the writing. The conclusion is that the use of WebQuest for writing task design facilitates scaffolding for the students. It is suggested that the feasibility of WebQuest for scaffolding the students be applied for other skill such as speaking, reading, and listening skills.